RAN-related neural-congruency: a machine learning approach toward the study of the neural underpinnings of naming speed - Christoforou, Christoforos; Theodorou, Maria; Fella, Argyro; Papadopoulos, Timothy C. (Frontiers in Psychology, 2023)
Objective: Naming speed, behaviorally measured via the serial Rapid automatized naming (RAN) test, is one of the most examined underlying cognitive factors of reading development and reading difficulties. However, the unconstrained-reading format of serial RAN has made it challenging for traditional EEG analysis methods to extract neural components for studying the neural underpinnings of naming speed. The present study aims to explore a novel approach to isolate neural components during the serial RAN paradigms that are informative of group differences between children with dyslexia and controls, improve the power of analysis, and are suitable for deciphering the neural underpinnings of naming speed. Methods: We propose a novel machine-learning-based algorithm that extracts spatiotemporal neural components during serial RAN, termed RAN-related neural-congruency components. We demonstrate our approach on EEG and eye-tracking recordings from 60 children (30 DYS and 30 CAC), under phonologically or visually similar, and dissimilar control tasks. Results: Results reveal significant differences in the RAN-related neural-congruency components between DYS and CAC groups in all four conditions. Conclusion: RAN-related neural-congruency components capture neural activity of cognitive processes associated with naming speed and are informative of group differences between children with dyslexia and typically developing children. Significance: We propose the resulting RAN-related neural-components as a methodological framework to facilitate the studying the neural underpinnings of naming speed and their association to reading performance and relating difficulties.